THE DETERMINANTS OF EXERCISING THE EXECUTIVE STOCK OPTION AND THE INCENTIVE EFFECT OF THE EXECUTIVE STOCK OPTION ON THE FIRM’S FINANCIAL RISK: EVIDENCE FROM CHINESE LISTED MARKET - Huang, Jing (International Journal For Research In Business, Management And Accounting, 2020)
This paper studies all the Chinese domestic listed companies that have issued executive stock options (ESO) from 2006-2012 and finds factors affecting their ESO exercising, like the ratio of exercising price relative to market price, financial performance (ROE), managerial ownership, and years to maturity (early exercising). This results explains why most of the Chinese ESOs have not been exercised in recent years of the economy recession. Furthermore, we examine the incentive effect of the ESO schemes on the listed companies’ financial risk and obtain an empirical evidence of “risk-taking” in the group of Chinese listed companies whose ESO have been exercised. The results suggest that the ESO schemes provide effective incentive for executives to take more risk if their stock options have been exercises, while the incentive effect is not significant before the options are exercised. Therefore, the volatile Chinese bear stock market makes the ESO schemes more fragile and less effective; and on the other hand, induces listed companies to take more risk against the market recession. To have an appropriate design of the ESO for the Chinese listed companies becomes challenging at present.